Why Internationalize Education? - Coelen, Robert (International Higher Education, 2015)
A number of predicted global developments are together creating a period of unprecedented change. The combined effects of the change of location of major business activity, the enhanced mobility of professionals, global redistribution of the middle classes, urbanization, the development of a globally interconnected network of new urban centers, job polarization, and technology, are producing an environment in which international awareness and intercultural effectiveness are no longer optional extras, but essential attributes for new graduates to exhibit. Indeed, if economic developments do not force the hand of higher education institutions in this respect, the need for the same attributes to address global challenges—such as climate change, the availability and distribution of food and water, and conflict–motivated migration—most certainly will.